2010
DOI: 10.1007/s00018-010-0539-8
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interactions between odorant-binding proteins of Anopheles gambiae

Abstract: To understand olfactory discrimination in Anopheles gambiae, we made six purified recombinant OBPs and investigated their ligand-binding properties. All OBPs were expressed in bacteria with additional production of OBP47 in the yeast Kluveromyces lactis. Ligand-binding experiments, performed with a diverse set of organic compounds, revealed marked differences between the OBPs. Using the fluorescent probe N-phenyl-1-naphthylamine, we also measured the binding curves for binary mixtures of OBPs and obtained, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
82
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 41 publications
10
82
0
Order By: Relevance
“…1C). That interactions with OBP1 are transmitted to residues that directly interact with the ligand may explain previous observations that the presence of OBP1 and OBP4 can lead to an increase in the binding affinity for a fluorescent dye (33). We conclude that binding of indole to OBP4 results in a significant increase in the conformational stability of residues that are required to allow interactions with OBP1.…”
Section: Binding Of Indole To Obp4 Leads To Formation Of a Bindingsupporting
confidence: 60%
See 4 more Smart Citations
“…1C). That interactions with OBP1 are transmitted to residues that directly interact with the ligand may explain previous observations that the presence of OBP1 and OBP4 can lead to an increase in the binding affinity for a fluorescent dye (33). We conclude that binding of indole to OBP4 results in a significant increase in the conformational stability of residues that are required to allow interactions with OBP1.…”
Section: Binding Of Indole To Obp4 Leads To Formation Of a Bindingsupporting
confidence: 60%
“…gambiae it was recently demonstrated that perception of indole and 3-methyl-indole requires OBP1 (31), and this may involve the formation of interactions between OBP1 and OBP4 (32,33). This study reveals that binding of indole to OBP4 results in a dramatic conformational ordering that is required to form a binding site for OBP1.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations